Antimicrobial minimum inhibitory concentration of Mycoplasma gallisepticum: a systematic review - Hossein, Taiyari; Nik Mohd Azmi, Nik Mohd Faiz; Abu, Jalila; Zakaria, Zunita (Elsevier, 2021)
The aptitude of Mycoplasma gallisepticum (MG) for changing its surface proteins allows the pathogen to reduce the efficacy of antimicrobial agents, especially those targeting surface proteins. Although antibiotic treatment cannot be a solution for the eradication of avian mycoplasmosis, it can be considered a good option to minimize the number of deaths. One of the challenges of antibiotic treatments is the development of antimicrobial resistance (AMR) among field isolates. Monitoring the antimicrobial susceptibility profile of field isolates can be a practical way of avoiding AMR. Thus, various tests have been developed to determine the antimicrobial susceptibility profile of field isolates. A modified broth microdilution minimum inhibitory concentration (MIC) test has been regularly used to measure the antimicrobial susceptibility profile of MG field isolates. Numerous studies have reported an increase in the number of antibiotic-resistant field isolates of MG. Therefore, this study presents a systematic review on antimicrobial MIC values of MG isolates to gather recent knowledge and investigate the prevalence and distribution of AMR among MG field isolates. A thorough search was conducted for related studies throughout 3 electronic databases. Altogether, 23 studies were identified as eligible studies and were used for further analysis. The results showed that enrofloxacin, oxytetracycline, and tylosin had the highest number of resistant isolates in most of the geographical distributions, respectively. Minimum inhibitory concentrations of these antibiotics need to be determined regularly to optimize treatment dosages.